Fighting against depopulation in inland Spain. Alternatives from Art, Design and Architecture - José-Luis Baró Zarzo; Javier Poyatos Sebastián; Nydia Martínez Martínez (Agathón)
The First Industrial Revolution brought about a mass influx of labour force to the cities from the countryside. In Spain, this migratory phenomenon accelerated during the period of development of the 1960s and continues to this day. Unless this is remedied many more villages will disappear in the coming decades, adding to the many deserted areas found in ‘empty Spain’. Many attempts, albeit half-hearted, have been made to reverse or at least put a stop to this territorial imbalance through economic policies such as support of agricultural activities, funding of entrepreneurship, and restoration of cultural heritage for the promotion of rural tourism. There is also an extensive range of imaginative popular initiatives for the repopulation of these municipalities, appealing especially to young people. This context serves as the starting point for this paper which focuses on the analysis of different strategies for the regeneration and survival of depressed rural villages based on architectural, urban, and artistic approaches in the areas of inland Spain.